Identification and antimicrobial activity of Micromonospora strains from Thai peat swamp forest soils - Somboon Tanasupawat; Chitti Thawai; Pawina Kanchanasin; Moriya Ohkuma; Takuji Kudo (My University, 2018)
Diversity and Versatility of Actinomycetes and its Role in Antibiotic ProductionHotam Singh Chaudhary,Bhavana Soni,Anju Rawat Shrivastava,Saurabh Shrivastava
Keywords: Swamp; Micromonospora; Identification; Fungal Biology and Applications